Automated systems for educational timetabling problems - Nguyen , Tan Tran Minh Khang; Tran, Hue Nuong (Journal of Technical Education Science, 2011)
This paper introduces UTS (University Timetabling System) and HTS (High school Timetabling System) - two web-based systems for solving the educational timetabling problems automatically. These systems support two timetabling problems named curriculum based course timetabling problem and high school timetabling problem, in which courses could have different lengths and could be divided into blocks. These two systems use Tabu Search-based algorithms as the kernel solvers and are applied to nine real-world instances of a university and three instances of two high schools in Vietnam. Results are obtained in reasonable time and the quality is promised for being used in practice